Gastrointestinal Dysfunction and Dysbiosis in Ischemic Stroke: Opportunities for Therapeutic Intervention - Rhiannon V. Macom; Candice M. Brown (Pharmaceuticals)
Although strokes originate in the brain, it is now widely appreciated that peripheral organ systems are also impacted by stroke. The gastrointestinal system is one peripheral organ system that is impaired during ischemic stroke. This impairment results in numerous complications, which impede post-stroke recovery. Many of the gastrointestinal mechanisms that contribute to the pathophysiology of ischemic stroke remain poorly understood. This review will highlight the molecular and cellular mechanisms underlying gastrointestinal outcomes in stroke by focusing on the complex interactions that largely occur in the small intestine. The final portion of this review will focus on therapeutic interventions that target the gut as a strategy to prevent or delay functional impairment and cognitive disability in stroke patients.